PiRNA hsa_pir_018849 promotes the proliferation and invasion of osteosarcoma cells by regulating the stability of CCN5 mRNA - Jiale Huang; Saishuai Yang; Peng Liu; He Jiang; Zhiming Cui; Jiajia Chen (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteosarcoma is a primary malignant bone tumor and that is predominantly found in adolescents and young adults, and it often occurs during periods of rapid bone growth. The precise specific etiology of osteosarcoma remains largely unknown. Piwi-interacting RNAs (piRNAs) are a class of small noncoding RNAs that are typically 24 to 31 nucleotides long, and they have potential therapeutic applications in diseases. Methods Small RNA sequencing and qPCR were initially used to detect differentially expressed piRNAs in the MG63 osteosarcoma cell line and in osteosarcoma tissues. The expression of hsa_piR_018849 in osteosarcoma cells was modulated using hsa_piR_018849 mimics and inhibitors. The impact of hsa_piR_018849 on the proliferation of osteosarcoma cells was assessed using CCK-8 and colony formation assays. Flow cytometry was used to investigate the effects of hsa_piR_018849 on osteosarcoma cell apoptosis. Cell scratch and Transwell assays were utilized to evaluate the impact of hsa_piR_018849 on the migration and invasion of osteosarcoma cells. mRNA sequencing was conducted to elucidate the mechanisms by which hsa_piR_018849 regulates osteosarcoma cell functions. Results Overexpression of hsa_piR_018849 promoted the proliferation, migration, and invasion of osteosarcoma cells while inhibiting apoptosis. Conversely, knockdown of hsa_piR_018849 suppressed osteosarcoma cell proliferation, migration, and invasion but promoted osteosarcoma cell apoptosis. Hsa_piR_018849 facilitated the proliferation of osteosarcoma cells in vivo. The expression levels of CCN5 were reduced by hsa_piR_018849. Hsa_piR_018849 reduced the stability of CCN5 by binding to the coding sequence (CDS) region of CCN5 mRNA. Conclusion PiRNA hsa_piR_018849 regulates the function of osteosarcoma cells by targeting and inhibiting the expression of CCN5.